Crop residues contribute minimally to spring-thaw nitrous oxide emissions under contrasting tillage and crop rotations. (January 2021) - Ferrari Machado, Pedro Vitor; Farrell, Richard E.; Bell, Gordon; Taveira, Caio J.; Congreves, Katelyn A.; Voroney, R. Paul; Deen, William; Wagner-Riddle, Claudia
Abstract: Crop residues are sources of carbon and nitrogen (N) after harvest, releasing inorganic N through mineralization or protecting soil N through immobilization. Inorganic N controls nitrous oxide (N2 O) emissions, a potent greenhouse gas (GHG) from agriculture. Hence, crop residues are accounted for as N2 O sources in national GHG inventories. For locations where post-harvest N2 O emissions occurs due to freeze-thaw, it is not known if crop residues contribute to emissions, and if tillage or residue type impact this contribution. This is of concern since crop residue and freeze-thaw emission factors (EF) may be 'double-counting' N2 O sources. We conducted an experiment over two non-growing seasons (NGS) in a long-term corn, soybean and winter wheat trial to (i) compare N2 O emissions for different crop residues within simple or diverse crop rotations under no-tillage (NT) or conventional tillage (CT); (ii) determine the importance of above- and below-ground residue addition to spring-thaw N2 O emissions as affected by rotation and tillage. A 15 N residue enrichment study was used to directly trace above- and below-ground residue 15 N into 15 N2 O fluxes and derive EF. Higher N2 O emissions were observed for CT than NT, regardless of rotation. Soybeans induced higher N2 O emissions than corn residue and the same crop residue (e.g. corn or soybean) showed trends of higher N2 O in the long-term diverse rotation. In all cases, crop residues contributed minimally to spring-thaw N2 O emissions (<2%), meaning differences in N2 O emissions were due to tillage and rotation effects on soil N availability, rather than by affecting crop residue N release for N2 O production. The NGS 6-month EF for crop residues never surpassed 0.05%, a minimal fraction of the annual 0.6% recommended EF. Refinement in emission inventories for cold climates should focus on freeze-thaw substrate release for N2 O production from other sources than crop residue. Graphical abstract: Image 1 Highlights: 15 N-labelled crop residue was traced into 15 N2 O flux during the non-growing season. Fluxes were measured in a long-term crop rotation and tillage trial. Differences in N2 O flux were observed between tillage, crop residue and rotations. Regardless of treatment, crop residue contributed <2% to spring-thaw N2 O emissions. Freeze-thaw based approaches do not 'double-count' crop residue emission factors.